The Role of Gastronomy in Shaping Tourist Experiences: A Study of Iloilo Province, Philippines - Noli A. LALLEN (Communications of International Proceedings, 2024)
This study investigates the influence of gastronomy on tourism in Iloilo Province, Philippines, addressing the gap in literature on the interplay between local culinary practices and tourism dynamics in this region. Utilizing a qualitative methodology, insights were gathered from a diverse group of stakeholders, including local chefs, restaurant owners, tourists, and farmers. The findings reveal that gastronomy plays a pivotal role in shaping Iloilo's cultural identity, serving as a medium for preserving and showcasing its rich heritage. Key local dishes such as talaba (oysters) and binakol (chicken soup), inasal, pancit molo, and most especially batchoy enhance the tourist experience, influencing their destination choices and likelihood of revisiting. The study underscores gastronomy's dual role as a cultural expression and an economic driver, contributing to local development, community engagement, and sustainability. The emphasis on local produce and sustainable practices highlights the region's commitment to environmental conservation and community empowerment. Integrating gastronomy more deeply into tourism strategies can significantly boost Iloilo Province's appeal and competitiveness as a tourist destination, setting a model for other regions.
Keywords: Gastronomy; Food Tourism; Tourist Experiences; Iloilo-Province Philippines